2017
DOI: 10.1080/17483107.2017.1373151
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and burdens: family caregivers’ experiences of assistive technology (AT) in everyday life with persons with young-onset dementia (YOD)

Abstract: The study found benefits for the FC, especially with simply designed AT, but also several barriers for successful use. A committed caregiver is vital throughout the process. Users will need professional advice and support, and occupational therapists may have a significant role in the process. Interventions implementing AT must be based on analysis of the needs of the person with YOD and the carers: their capabilities, preferences, embodied habits, and coping strategies. Implications for Rehabilitation Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…In the interest of brevity, only the first 60% will be listed. The intervention most often noted was an interview [3,[22][23][24][25]29,31,39,43,44,49,57,59,61,63,65]. Researchers interviewed users of AT (PWD and carers) in 16/48 studies (33%).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the interest of brevity, only the first 60% will be listed. The intervention most often noted was an interview [3,[22][23][24][25]29,31,39,43,44,49,57,59,61,63,65]. Researchers interviewed users of AT (PWD and carers) in 16/48 studies (33%).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The most common form of bias was selection bias. Examples of selection bias were all: participants had experience with technology [23], same site [25,28,30,34], or a disproportionately large sample that was male [22,30,36]. These examples of bias limit the external validity of the results.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Berge () showed that family caregivers’ primary concern is safety, and the caregivers encourage use of telecare as they expect it to enhance safety. Previous research has shown that technology may help reduce family caregivers’ perception of task‐specific burdens (Mortenson et al, ) and provide increased feelings of relief (Holthe, Jentoft, Arntzen, & Thorsen, ), which is important in the light of the stress the family caregivers may experience.…”
Section: Introductionmentioning
confidence: 99%
“…After years of trials and a policy of using telecare to promote active ageing and ageing in place, there is a need for a better understanding of persistent engagement with telecare (Cook et al, ; Karlsen et al, ; Lynch, ) from older adults and their family caregivers’ perspectives (Holthe et al, ). The present study seeks to enrich insight into clinical practice and models of telecare service delivery, by exploring how telecare may meet the older adults’ needs.…”
Section: Introductionmentioning
confidence: 99%